1983
DOI: 10.1046/j.1468-2982.1983.0303143.x
|View full text |Cite
|
Sign up to set email alerts
|

Glossopharyngeal Neuralgia

Abstract: A review is presented of the clinical features of glossopharyngeal neuralgia, as analysed from 304 reported instances. The sex-ratio of the condition is equal, the peak-age at onset is between 40 and 60 yrs, and left-side involvement predominates in females. The clinical features are detailed in 18 specific items. In a review of the aetiology it is argued that the so-called "idiopathic" type of IXth nerve neuralgia (which, upon careful analysis, may still rest upon either an obscure tumor or infection or elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
9

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 84 publications
(94 reference statements)
2
40
0
9
Order By: Relevance
“…As a result, no sex effect could be identified [53]. With regard to vagoglossopharyngeal neuralgia, researchers reported that there was no preponderance regarding sex [54,55]. I gave a supplementary explanation for the term "vagoglossopharyngeal neuralgia".…”
Section: Vagus Nervementioning
confidence: 99%
“…As a result, no sex effect could be identified [53]. With regard to vagoglossopharyngeal neuralgia, researchers reported that there was no preponderance regarding sex [54,55]. I gave a supplementary explanation for the term "vagoglossopharyngeal neuralgia".…”
Section: Vagus Nervementioning
confidence: 99%
“…Mechanical stimulation of the fauces by swallowing, talking, and coughing typically triggers the pain. 15 Specific features of pediatric neuralgia include scarcity of pain free episodes and an exaggerated debilitation leading to performance lack in essential activities. 7 Glossopharyngeal neuralgia in the young has the potential to lead to developmental disorders, as the pain prevents the pediatric patient from eating.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Glossopharyngeal neuralgia is a rare disease occurring mostly in women aged between 40 and 60 years 23 . Pain is usually incapacitating, unilateral, affecting the posterior oropharynx, tonsillar fossa and base of the tongue, extending to the ear.…”
Section: Glossopharyngeal Neuralgiamentioning
confidence: 99%